Pharmacobotanical study and phytochemical prospection of Mirabilis jalapa L. - Gabriel Melo Santana; Carlos Henrique da Silva Ribeiro; Felipe Ribeiro Silva; Cledson dos Santos Magalhães; Karina Perrelli Randau (Universidade Estadual de Alagoas, 2023)
Mirabilis jalapa L., popularly known as "Maravilha", belonging to the family Nyctaginaceae Juss., is used in folk medicine to treat leukorrhea, itching, swelling, among other diseases. The study aimed to describe anatomical characteristics of root, stem and leaf; identify the sites of accumulation of metabolites in the leaves and perform phytochemical prospecting of the leaves of M. jalapa. In the study, the usual methods in plant anatomy were used in the preparation of the analyses of semi-permanent slides containing cross-sections of the root, stem, petiole and leaf blade and paradermal leaf blade of M. jalapa. Histochemical tests were also performed in order to locate the metabolites in the leaf blade through cross-sections and phytochemical prospection of methanolic extracts of the leaves, by means of Thin Layer Chromatography. For the root, layers of periderm and pheloderm were observed; on the stem the presence of phloem both near the xylem and the sclerenchyma; in the leaf blade, raffide-type crystals were observed only in the mesophyll region, and presenting amphistomatic leaf blade. For histochemistry it was observed that the crystals are calcium oxalate, in addition to observing phenolic compounds, alkaloids, steroids, lipophilic compounds and lignin. In the phytochemistry was identified mono and sesquiterpenes, triterpenes and steroids, flavonoids, cinnamic derivatives and reducing sugars. The results presented are fundamental for the quality control of the plant drug and the pharmacobotanical standardization of the studied species.